Investigating the Interplay of Social and Biological Factors on Mathematics Anxiety among Senior Secondary Students - Asanre, Akorede Ayoola; Sondlo, Aviwe; Adekunle, Ridwan Ayomide (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study investigates the social and biological factors influencing mathematics anxiety among senior secondary school students in Sagamu Local Government Area, Ogun State, Nigeria. Data were gathered using a descriptive survey methodology, 500 students across five secondary schools using simple random sampling techniques. A standardized questionnaires Social Factor Questionnaire (SFQ, r=0.82), Biological Factors Questionnaire (BFQ, r=0.73) and Abbreviated Math Anxiety Scale (AMAS, r=0.84). Descriptive statistics (mean and standard deviation) and Pearson correlation analysis were used to analyze the data. Results reveal that family pressure, inappropriate teaching methods, the school environment, neurological responses to stress, and age and developmental stage are significantly related to mathematics anxiety among senior secondary school students. Conversely, learners' behaviour, genetic predispositions, and gender do not significantly affect mathematics anxiety. Therefore, the study recommends that schools s implement parent-teacher programs and counselling service to reduce family pressure and foster a supportive home environment for students.